ANALISIS CUALITATIVO DE LA SOLIDIFICACION DEL SISTEMA BINARIO PbSb - Flores, L. (2006)
When to chill an alloy PbSb since the temperature of strained, the size of the grains will be determined by the relation between the rapidity of growth and the rapidity of nucleation. It was utilized the curves of cooling off and an analysis was carried out metallographic to identify the microstructure of this, utilizing the balance of heat was calculated the latent heat of fusion. The study of the caloric transfer in a system metal-mold was carried out by means of discreet numerical solutions, considering the transformation of liquid-solid phase and the convexion natural between the phase liquid and thick of the alloy. The methods utilized were the method of finite volume and the method of line to line. A subcooling off in the sample is observed 3, due to the slow velocity of cooling off, also the size of grain is greater in the sample 1 and the solidification is formed 2 solid phases, with a structure eutectic (formed by the phases α and β) and the phase β primary.